1996
DOI: 10.1007/bf01938870
|View full text |Cite
|
Sign up to set email alerts
|

The action of the peptidoleukotriene LTD4 on intracellular calcium in rat mesangial cells

Abstract: The dose-dependent effect of CGP 45715A on the LTD4-induced Ca2+ response of glomerular mesangial cells has been studied. Our results demonstrate that the LTD4-dependent increase in the cytosolic Ca2+ concentration primarily involves an InsP3-mediated release of Ca2+ from intracellular storage sites and to a minor extent an enhanced influx of Ca2+ through receptor-operated Ca2+ channels located in the plasma membrane. The action of CGP 45715A on the Ca2+ response is an inhibitory one and is convincingly explai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
1

Year Published

1997
1997
2003
2003

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 41 publications
0
5
1
Order By: Relevance
“…Indeed, in our previous report [36], treatment of PTCs with 8Br-cAMP inhibited the Na + uptake in a dose-dependent manner. However, these results are inconsistent with those of reports in which LTD 4 was found to reduce rapidly the intracellular cAMP content in guinea pig trachea and lung parenchyma and rat mesangial cells [8,37]. The LTD 4 -induced decrease of cAMP generation inhibits the activity of cAMP-dependent protein kinase A which causes the cell response [38].…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…Indeed, in our previous report [36], treatment of PTCs with 8Br-cAMP inhibited the Na + uptake in a dose-dependent manner. However, these results are inconsistent with those of reports in which LTD 4 was found to reduce rapidly the intracellular cAMP content in guinea pig trachea and lung parenchyma and rat mesangial cells [8,37]. The LTD 4 -induced decrease of cAMP generation inhibits the activity of cAMP-dependent protein kinase A which causes the cell response [38].…”
Section: Discussioncontrasting
confidence: 56%
“…The hydrolytic products of phospholipase C are inositol triphosphate and diacylglycerol which are both plausible second messengers for LTD 4 . Several lines of evidence have also shown that cells stimulated with LTD 4 cause a prompt and transient increase in [Ca 2+ ] i at nanomolar concentrations [8,34]. This LTD 4 -triggered cytosolic free Ca 2+ transient is generated by both an intracellular mobilization of Ca 2+ and an influx of Ca 2+ over the plasma membrane.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In human detrusor smooth muscle cells, it was reported that elevation in [Ca 2ϩ ] i levels evoked by LTD 4 were almost exclusively due to mobilization from intracellular Ca 2ϩ stores (4). In other target cells, the LTD 4 -evoked Ca 2ϩ response was dependent on the release of Ca 2ϩ from intracellular stores and enhanced Ca 2ϩ influx (20,23). The present study demonstrates that both ANG II-and CysLTevoked increases in [Ca 2ϩ ] i levels were significantly attenuated by 2-APB.…”
Section: Discussionmentioning
confidence: 99%
“…They exert their actions via activation of at least two pharmacologically defined G proteincoupled receptors (CysLT 1 and CysLT 2 ) that are linked to PLC-mediated Ca 2ϩ mobilization (8,16). In addition to their well-known bronchiolar smooth muscle spasmogenic effect, these inflammatory mediators have been shown to enhance contractile responses in smooth muscle preparations or [Ca 2ϩ ] i levels in their target cells (4,10,20,21,23,29,30). Recently, with the use of a variety of techniques including in situ hybridization, Northern blotting, and RT-PCR, the presence of CysLT 1 and/or CysLT 2 transcripts in cardiac tissue has been identified (8,10,16,21).…”
Section: -Lipoxygenase (5-lo) or 3-[[[3-[2-(7-chloro-2-quinlinyl)ethmentioning
confidence: 99%